(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing has become a reality with new IT infrastructure based on several techniques such as distributed computing, virtualization, etc. Besides the many benefits that they can offer, cloud computing also comes with the difficulty of protecting data security. This paper first explores the basic concepts and analyzes the main aspects of data security about cloud computing. We then look at each problem, discussing its nature and existing solutions, if any. In particular, we will pay special attention to protecting data confidentiality/integrity/availability, data access, and monitoring, and complying with rules and obligations to ensure data security and confidentiality. With the fast advancement of organizing and portable gadgets, we are confronting a dangerous incensement of swarm sourced information. Existing frameworks as a rule depend on a confided in server to total the spatio fleeting publicly supported information and after that apply differential security component to bother the total insights previously distributing to give solid protection ensure. We propose a Modified appropriated specialist based protection saving structure, called MDADP that presents another dimension of various operators between the clients and the untrusted server.